Designing Autism-Friendly Learning Space through Integrating Autistic Behavior and Motion Space Mapping - Brainnisa Ramadhani Nur Nisrina; Tiara Ika Widia Primadani; Michelle Nadine Santoso; Yuvita Wulan Tanemaru (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DRPM), ITS, 2025)
The increasing number of students with autism in Indonesia has encouraged the development of therapy and educational service centers, including in Malang. At PKBM Ki Hadjar Dewantara, a non-formal educational institution, a notable rise in students diagnosed with autism spectrum disorder (ASD) has been recorded. This study focuses on understanding the behavioral characteristics of autistic students within classroom settings. Autism, as a developmental condition, affects social interaction, communication, emotional regulation, sensory processing, play, and repetitive behavior. Using a qualitative approach, the research employed empirical observation, interviews with educators and therapists, and behavior setting techniques through motion space mapping. The findings highlight the importance of autism-friendly learning spaces, organized into four adaptive zones: the play zone (high stimulation), the learning and creativity zone (transitional), the escape or safe zone (low stimulation), and the multisensory zone (Snoezelen). This zoning strategy reflects an inclusive and adaptive design that accommodates diverse sensory and behavioral needs. The study demonstrates how flexible spatial design in non-formal education can foster engagement, comfort, and development for autistic students while supporting sustainable and inclusive learning practices.